RAQAMLI TA’LIM JARAYONIDA BOʻLAJAK OʻQITUVChILARNING AXBOROT TEXNOLOGIYALARI BO‘YIChA FUNDAMENTAL BILIMLARINI ORTTIRISh - Ilyasova, Z.K. (SCIENCE and SOCIETY, 2025)
The article will focus on acquiring fundamental knowledge about information technologies for future teachers in the process of digital learning. The fundamental content of the course on the application of information technology in professional activities in pedagogical higher educational institutions is presented in a form appropriate to the educational directions of future teachers.
Keywords: education; digital technologies; computer science; universal educational activities; information-communication technologies; fundamentality; e-learning materials; e-learning courses